Developing AYOPANEN Applications for Sharia-Based Agricultural Investment Management - Imelda, Maritha; Eko Wulandari, Sri Hariani; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
AYOPANEN is an application engaged in agriculture. This application was formed because it was motivated by the Minister of Trade's appeal to the community which was expected as an off taker to replace the role of middlemen and cooperate with the farmers. In addition, labor in agriculture, livestock and fishery sectors still have difficulty in increasing their business productivity due to constrained capital factor. Difficult access to capital causes the product since planted has been taken by the middleman. So when the harvest is done that determines the selling price is the middleman. The solution to be given is a web-based application that can help farmers get capital from investors to manage agriculture using As-Salam investment method, where the traded product is not available when the transaction is made, and the buyer makes the initial payment with the quality characteristics clear product while delivery of products will be done in the future. Existing processes in the application are product management for farmers, investment purchases by investors, As-Salam agreement documents, progress tracking, admin validation, and transaction reports. The results show that this application can help investors find agricultural products that want to be invested with the characteristics of clear product quality. Applications can help farmers get a capital loan without paying interest on the loan